Identification and Comparison of Constituents of Aurantii Fructus and Aurantii Fructus Immaturus by UFLC-DAD-Triple TOF-MS/MS - Yang Bai; Yuying Zheng; Wenjing Pang; Wei Peng; Hao Wu; Hongliang Yao; Panlin Li; Wen Deng; Jinle Cheng; Weiwei Su (Molecules, 2018)
Although Aurantii Fructus (AF) and Aurantii Fructus Immaturus (AFI) are both the fruits of the same rutaceae plant at different stages of growth, they exert similar yet distinct clinical effects. The chemical composition is crucial for quality control as well as therapeutic application. To address this concern, it is significant to evaluate the similarities and differences of the constituents in both AF and AFI. The extract of AF and AFI were comprehensively analyzed by ultra fast liquid chromatography-photodiode array detector-triple-time of flight-tandem mass spectrometry (UFLC-DAD-Triple TOF-MS/MS). Among the 40 compounds detected, 19 metabolites were detected in both the AF and AFI; whereas 13 compounds were only detected in AF and five constituents were exclusively detected in AFI. In particular, even in AFI, three compounds were only identified in AFI (Citrus aurantium’ L. and its cultivar). Among the 18 compounds confirmed by standard database, 13 compounds were reported in AF and AFI for the first time. Furthermore, the distinction was also revealed by the content of naringin, hesperidin, neohesperidin, and synephrine. The study directly contributed to the similarities and differences of AF and AFI. Herein, similarities and the differences in chemical profiles of AF and AFI could explain the current clinical applications.